(untitled) (Jurnal Sitakara, 2026)
This study aims to explore the learning motivation of eighth-grade students in music education through the use of regional pop songs at SMP Negeri 6 Semarang. The research focuses on the implementation of regional pop songs in the learning process and the students’ learning motivation. Theoretical foundations are based on music education and learning motivation. The research adopts a mixed-method approach using a sequential exploratory model, starting with a qualitative analysis through a phenomenological approach, followed by a descriptive quantitative analysis. Data were collected through interviews, observations, documentation, and questionnaires. The findings indicate that regional pop songs have been effectively implemented as learning materials, supporting students’ understanding of the content and enhancing their motivation to learn. Students responded positively to the use of regional pop songs, as the materials felt more relatable and engaging. High levels of learning motivation were reflected in the average scores for learning interest (29.5469), active engagement (29.3437), and learning satisfaction (29.4063). These scores demonstrate students’ interest, active participation, and satisfaction in music education. The study concludes that the use of regional pop songs has a positive impact on students’ learning motivation in music education. Keywords: Music Education; Regional Pop Songs; Learning Motivation.